Peningkatan Kreativitas Siswa melalui Implementasi Profil Pelajar Pancasila Rahmatan Lil ‘Alamin (P5-PPRA) di MTSN 1 Tanah Datar - Azahra, Amertya; Kosim, Muhammad (ISLAMIKA, 2024)
This research aims to describe 1). P5-PPRA Planning in MTSN 1 Tanah Datar 2). Implementation of P5-PPRA at MTSN 1 Tanah Datar 3). Inhibiting factors in implementing P5-PPRA at MTSN 1 Tanah Datar. The method used in this writing uses a qualitative library research approach and interviews. In this method, data is collected through several literature such as books, journals and sources that support this discussion. The results of the research show that 11) the design of P5-PPRA at MTSN 1 Tanah Datar is good and has been discussed first before applying P5-PPRA to students who pay attention to the creativity of students and also teachers. 2) the implementation of P5-PPRA is in accordance with the process that has been held together by the facilitator team where students have been given the topic of recycling eggshell waste into calligraphy, and this shapes students' creativity. 3) The obstacles to P5-PPRA at MTSN 1 Tanah Datar are lack of facilities and infrastructure, little time and educators who still do not fully understand P5-PPRA.